Minutiae Based Fingerprint Recogntion (International Journal of Engineering and Computer Science, 2017)
Biometric Recognition is the recognition of an individual by using biometric features. The biometric recognition is done by many different features like iris, face, palm, fingerprint, voice, etc. Each biometric has its strengths and weakness and the choice of biometric feature depends on the requirement of the system. In this paper, fingerprint feature is used and its various steps for the recognising any individual. In this paper, the various strategies/methods are used for each step of fingerprint recognition. The fingerprint recognition has many applications like identification of user, time and attendance system, device access control, forensic identification, etc.